Monitoring and evaluating the effect of the working environment factors on health of staff in the magnesite mine in Slovak Republic - RODA, STEFAN; FABIANOVÁ, ELEONÓRA; GAJDOSOVÁ, DAGMAR; GAJDOS, ONDREJ; VIDOVÁ, PAULÍNA (Boletim Paranaense de Geociências, 2002)
In this large-scale study goal to contribute to the understanding of aetiology of encephaloid lung tumour affections of various underground workers, we tried to evaluate the dependency between health and working environment in magnesite mines. Mining is done in underground places with minimal weight and the important measure of an exploitation locomotive mechanization with gas-engines. The important technological changes of raw materials extraction brought also the important qualitative changes in the composition of the unhealthy factors of the working environment, where the chemical risk factors have greater importance. The working air assimilates into the mixture of various solid, liquid and fluid risk factors, which do not affect the organism separately but only with relative interactions. There originates the assumption that the workers exposure to specific mining aerosol with the non-special, toxic and late effects on human organism. The offered work has got the goal to estimate the health risk i.e. to define odds and size of eventual health changes at workers in a simulation magnesite factory in Jelšava like a result of exposure factors which are created by mining aerosol. The topic of interest was the rate of lung cancer risk from the exposure of diesel air pollutants and their selected carcinogenic elements. The exposure inhalation model was worked out for workers and total working risk was estimated in dependence on the exposure in critical professions. The results create basic document for goal-directed epidemiological study, which is the type of case control for the purpose of identification of possible working exposures in relation to lung tumour affection.